Rancang Alat Magnetic Separator Untuk Meningkatkan Kadar Bijih Timah Di Laboratorium Teknik Pertambangan Universitas Bangka Belitung - Janiar Pitulima; E.P.S.B Tamantono E.P.S.B Tamantono; Haslen Oktarianty (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2019)
Magnetic separator testing uses two variables, namely the speed of the roller on the conveyor belt andthe feed speed. Due to the minimum number of variations that can be used in magnetic separatortesting, roller speed testing is used at 0.6 m / s and 0.7 m / s. the variation of figures at the feedingspeed of 0.21 kg / s and 0.35 kg / s so that 8 samples obtained from the processing of a magneticseparator with 4 magnetic samples and 4 non-magnetic samples. The feed samples used wereprepared by drying and sifting into 3 size fractions to be used in the grain counting analysis process sothat the percentage of minerals contained in the sample were found: 15.82% Cassiterite, 63.95%Ilmenite, 6.09% Monazite, 0.48% Pyrite / Marcasite, 1.61% Zircon, 1.44% Topaz, 0.65% Tourmalineand 9.96% Quartz. The effect of roller speed on the increase tin ore content is still common, this isbecause there are not many experiments carried out so that taking the trend of the influence of theroller speed is too fast. The effect of feed speed, the greater the feed speed on the magneticseparator, the smaller the tin ore content obtained.